Realization of acoustic spin transport in metasurface waveguides - Yang Long (Nature Portfolio, 2020)
Spin angular momenta play a crucial role in topological phases of matter, in acoustic waves they have been demonstrated recently. Here, the authors present a symmetry-breaking metasurface waveguide that assists backscattering suppression of acoustic waves, because of tight spin-momentum coupling.